Indigenous knowledge and herbs recognition among students of Foundation in Science Programme at Centre of Foundation Studies, UiTM Cawangan Selangor, Kampus Dengkil: a case study / Siti Sabrina Kasri ... [et al.] - Kasri, Siti Sabrina; Ishak, Nur Syakireen; Saidon, Nhawal Aminie; A. Hamid, Nor Hafizah; Pardi, Faezah (2019)
With no doubts, the values of Malaysian herbs plant are not only limit to its medicinal benefits but also in local knowledge of each herb plant. Ethnic Malays, bumiputera Semenanjung, Sabah and Sarawak are well known for the practical use of herbs plant in everyday life. However, in assessing whether the younger generation has general knowledge and recognize the Malaysian herbs plant, it is unclear. This is because the indigenous knowledge about herbs plants is normally transferred by the elder people. Hence a, case study was conducted among 236 students of Foundation in Science program at the Centre of Foundation Studies, UiTM Cawangan Selangor Kampus Dengkil. The objective of the study was generally to see their level of indigenous knowledge which includes their understanding and recognition towards 20 type of herbs plants that were very common to be grown in Malaysia. The study was carried out using questionnaire survey. Our studies shown that overall 236 students have indigenous knowledge and able to recognize the herbs plant.